Confessions of a serial biographer - Rollyson, Carl E. (Carl Edmund) (McFarland & Company, Inc., 2016)
"This memoir of a professional biographer's life tells the inside story of how he became interested in subjects and reveals the mechanics of the trade: how to assemble proposals for publishers, conduct interviews and archival research, and joust with editors, subjects and their literary estates. Other biographers have described their process but remained discrete, not wishing to offend"--